Јужнославистиката како интеракадемски предизвик и нова културна парадигма - Banovikj-Markovska, Angelina (Национално издателство за образование и наука „Аз-буки“, 2019)
This paper addresses the perspectives of the South Slavic interlingual and intercultural community, as a regional semiosphere and an interacademic / interuniversity challenge within the European polycultural and polydiscursive space. The awareness of the similarities between South Slavic languages, literatures and Cultures, their mutual insights, recognition and acknowledgments could be an alternative challenge in the revitalization of neglected relations between universities and a new cultural paradigm that strives for a »regional pluralism« with a polycentric and diverse structure.
Keywords: South-Slavic; Inter-Academical/Interuniversity challenge; Interpretative Communities; Regional pluralism; globalization